Factor influencing employee turnover intention at Megah Transport Sdn Bhd, Ipoh Perak / Fatima Athirah Zakri - Zakri, Fatima Athirah (2019)
Employee turnover issue has become crucial to most organizations because it can give negative impacts to the organization such as low productivity and unstable financial performance. Thus, organizations need to find out the solution to reduce the employee turnover intention. However, employee turnover intention in logistic sector has not received sufficient attention in the past literature. To date, there are only several studies that have been conducted in other sectors such as hospitality and education sector. Therefore, this research was conducted to study the relationship between organizational commitment, organizational justice and job satisfaction with employee turnover intention at Megah Transport Sdn Bhd which is logistic sector. A set of structured questionnaires was administered to 162 employees who are working at Megah Transport Sdn Bhd. The data was analyzed using Statistical Package for the Social Sciences (SPSS). Result revealed that organizational commitment, organizational justice and job satisfaction has significant relationship with employee turnover intention. The recommendations for future research were also discussed.